2014
DOI: 10.1093/cid/ciu714
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Asymptomatic Respiratory Viral Infections in the First Year of Life: Association With Acute Otitis Media Development

Abstract: Compared to symptomatic infection, asymptomatic viral infection in infants is associated with young age, male sex, low viral load, specific viruses, and single virus detection. Asymptomatic viral infection did not result in AOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 29 publications
10
87
0
4
Order By: Relevance
“…None of the infants were hospitalised. In a similar study of a panel of viruses by CHONMAITREE et al [8] a virus was identified in 795 (39%) of samples, with two or more viruses in 228 of these. Predictably, rhinovirus was the most commonly identified virus.…”
Section: Identification Of Pathogens and Relationship To Disease Andmentioning
confidence: 84%
“…None of the infants were hospitalised. In a similar study of a panel of viruses by CHONMAITREE et al [8] a virus was identified in 795 (39%) of samples, with two or more viruses in 228 of these. Predictably, rhinovirus was the most commonly identified virus.…”
Section: Identification Of Pathogens and Relationship To Disease Andmentioning
confidence: 84%
“…Several studies showed that children who attend day-care centres have an increased risk of ARI, due to the close contact among each other, thus increasing the viral transmission (2,3,34). Moreover, the data was collected in winter, so there was a high frequency of ARI due to seasonality (1,35).…”
Section: Discussionmentioning
confidence: 99%
“…Parents make a considerable use of healthcare services to cope with ARI, thus becoming a burden for children and their families (1,4). Furthermore, ARI are the main cause of worldwide morbidity, leading to school and work absenteeism (5).…”
Section: Introductionmentioning
confidence: 99%
“…WBC counts and CRP levels are of limited value, and the significance of RV loads as a surrogate marker of disease severity is still inconclusive (10,(46)(47)(48). Our study introduces a proof of concept: The combination of molecular microbiological data and systemic host responses could help in assessment of the significance of pathogen detection and the causality of clinical illness.…”
Section: Original Articlementioning
confidence: 93%